Prevalence of Depression among elderly population: A cross-sectional study - Rai, N; Pokhrel, P; Shakya, DR; Sapkota, N; Basnet, M; Sharma, P P (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: The elderly population is on rise in Nepal. With increasing elderly population, the burden of elderly health problems is also increasing. The number of mentally ill elderly is on rise. Studies have shown Depression is most common psychiatric illness in geriatric population 3 which has a significant impact in quality of life of elderly people.This study was carried out to examine the prevalence of Depression among elderly population visiting psychiatric services and severity of illness. Material And Method: It is a descriptive, cross sectional, hospital based study. A total of 60 patients of age 60 and above, attending psychiatric services were enrolled after due written informed consent. The study period was 6 months (2012-2013). A semi-structured proforma was used to collect information about the socio-demographic profiles of patients. Diagnosis was made based on International Classification of Diseases (ICD-10) criteria after discussion and assessment of the case with the consultant psychiatrist. Results: The maximum number of patients was in the age group of 60-69 (n=43, 71.7%). The mean age was 68.18. The predominant caste was “caste origin hill hindu group” (n=30, 50.0%). Maximum cases were Hindu (n=45, 75.0%) by religion. Majority of the subjects were female (n=36, 60.0%). Most of the subjects were married (n=48, 80%) and were from middle socio economic status (n=44, 73.3%) and majority (n=35, 58.33%) of the patients were illiterate. The prevalence of depression was 50.0%. Among them majority were suffering from moderate depressive episode (n=15, 53.6%). Majority of them were female. Among the 30 depressive patients, 11 (36.7%) patients had positive family history of mental illness. Among the mental illness, Mood disorder (n=5, 45 .5%) and anxiety disorder (n=3, 27.3.0%) were found to be the most. Conclusion: Overall findings suggest that prevalence of depression is common, so further research is required to understand the gravity of situation. J Psychiatrists’ Association of Nepal Vol. 6, No. 2, 2017